2022
DOI: 10.1177/11795549221123617
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for Metastatic Gastric Cancer: Does Age Matter? A Single-Center, Retrospective, Real-World Study

Abstract: Background: Palliative chemotherapy is the preferred standard of care for patients with metastatic gastric cancer (mGC). It remains uncertain whether older patients with mGC would benefit from palliative chemotherapy. This study aimed to investigate the clinical impact of palliative chemotherapy in older patients with mGC. Methods: This single-institute, retrospective, and real-world study included 428 patients with mGC between January 2009 and December 2019. Among them, 306 who received palliative chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…divided 306 patients receiving palliative chemotherapy into two groups at the age of 70 years and compared the clinical demographics, prognosis and hematological toxicity of chemotherapy between the two groups. It was found that the progression-free survival and overall survival were the same and the incidence of hematological toxicity was similar ( 91 ), which suggests that age is not a limiting condition for palliative chemotherapy in elderly patients with metastatic gastric carcinomas.…”
Section: Palliative Chemotherapymentioning
confidence: 99%
“…divided 306 patients receiving palliative chemotherapy into two groups at the age of 70 years and compared the clinical demographics, prognosis and hematological toxicity of chemotherapy between the two groups. It was found that the progression-free survival and overall survival were the same and the incidence of hematological toxicity was similar ( 91 ), which suggests that age is not a limiting condition for palliative chemotherapy in elderly patients with metastatic gastric carcinomas.…”
Section: Palliative Chemotherapymentioning
confidence: 99%
“…8 In another retrospective study, 306 patients receiving chemotherapy treatment were divided into two categories under and over 70 years of age and no statistically significant difference was found in progression-free survival (PFS) and OS between the two groups. 9 The aim of our study was to compare the efficacy and side effects of single-agent and double-agent chemotherapy regimens in the first-line treatment of patients with HER-2 negative metastatic GC aged 80 years and older, which is part of our routine practice.…”
Section: Introductionmentioning
confidence: 99%